Self-polymerization of dopamine on zinc oxide nanoparticles for enhanced corrosion resistance in epoxy-aluminum coatings - Albarqouni, Yasin M.Y.; Nurul Huda, Abu Bakar; Thalji, Mohammad R.; Arman, Abdullah (Elsevier Ltd, 2025)
Conventional organic coatings often face limitations in providing long-term corrosion protection in aggressive environments. This study introduces a dual-functional polydopamine-25 zinc oxide (PD-Z) composite incorporated into an epoxy (EP) matrix (PD-Z/EP) to enhance the hydrophobicity and corrosion resistance of aluminum substrates. Characterization analyses confirmed the successful fabrication of the PD-Z composite. Electrochemical measurements, specifically potentiodynamic polarization, are conducted after three days of immersion in a 3.5 wt% NaCl solution, significantly decreasing corrosion current density (Icorr) from 249.4 nA.cm−2 for pure EP to 167 nA.cm−2 for PD-Z/EP. Concurrently, the corrosion rate decreased from 0.004 to 0.0002 mm.y−1. Additionally, electrochemical impedance spectroscopy (EIS) demonstrated a marked increase in the low-frequency impedance modulus (|Z|₀.₀₁ Hz) from 0.07 × 106 Ω.cm2 to 1.2114 × 106 Ω.cm2, indicating superior corrosion inhibition. The exceptional anodic and cathodic protective performance of the PD-Z/EP coating is attributed to the synergistic effects of polydopamine and ZnO, which enhance chloride ion entrapment, hydrophobic barrier properties, and overall corrosion resistance.